Building Customer Loyalty Through Local And Religious Values - Prabowo, Galuh; Purnomo, Muhammad Sidiq; Duerapho, Zulfa; El Fayoumi, Ziyad (QUALITY, 2025)
This study aims to analyze how value-based marketing management rooted in local and religious values can strengthen customer loyalty toward Islamic boarding schools, with a focus on Muadalah Ulya Darussalam Blokagung Banyuwangi. This study uses a qualitative approach with a case study design to analyze the role of marketing management based on religious and local values at Muadalah Ulya Darussalam Blokagung. Data were collected through in-depth interviews, observations, and documentation. The data were then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions.  The study reveals that value-based marketing management rooted in religious and local culture at Muadalah Ulya Darussalam Blokagung builds strong trust and loyalty among parents. Aligning institutional and parental values creates emotional bonds and reinforces confidence in the education provided. Integrating local customs and religious traditions strengthens the school’s identity and connection with the community. These findings highlight the effectiveness of value-based strategies in building long-term relationships and competitiveness. Educational institutions can adopt similar approaches by embedding cultural and religious values into programs and activities, thus enhancing trust, loyalty, and institutional relevance in their communities.